COVID-19 symptoms over time: comparing long-haulers to ME/CFS. Issue 2 (3rd April 2021) - Jason, Leonard A.; Islam, Mohammed F.; Conroy, Karl; Cotler, Joseph; Torres, Chelsea; Johnson, Mady; Mabie, Brianna
ABSTRACT: Introduction: Our objective was to determine which symptoms among long-hauler COVID-19 patients change over time, and how their symptoms compare to another chronic illness group. Methods: 278 long-haulers completed two symptom questionnaires at one time point, with one recounting experiences during the first two weeks of their illness, an average of 21.7 weeks prior. We used a comparison group of 502 patients diagnosed with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Participants completed a standardized symptom questionnaire and a list of additional CDC COVID-19 symptoms. Results: Over time, the long-haulers reported an overall reduction of most symptoms including unrefreshing sleep and post-exertional malaise, but an intensification of neurocognitive symptoms. When compared to ME/CFS, the COVID-19 sample was initially more symptomatic for the immune and orthostatic domains but over time, the long-haulers evidenced significantly less severe symptoms than those with ME/CFS, except in the orthostatic domain. Among the COVID-19 long haulers, several neurocognitive symptoms got worse over time, whereas improvements occurred in most other areas. Conclusions: These types of differential patterns of symptoms over time might contribute to helping better understand the pathophysiology of those reporting prolonged illness following COVID-19.